Uzmanības deficīta un hiperaktivitātes sindroms pirmsskolas un jaunākā skolas vecuma bērniem - Medniece, Elīna (Latvijas Universitāte, 2017)
Uzmanības deficīta un hiperaktivitātes sindroms (UDHS) ir viens no visbiežāk sastopamajiem psihisko traucējumu veidiem bērnībā, kas izplatīts visā pasaulē. Parasti tiek novērots skolas vecuma bērniem, bet var sākties jau pirmsskolas vecumā. Galvenās izpausmes ir neuzmanība un/vai hiperaktivitāte-impulsivitāte, kas ir neatbilstoša pacienta vecumam un attīstības līmenim, tādējādi traucējot indivīda sociālo, akadēmisko/profesionālo funkcionēšanu. Bērnībā līdzās UDHS bieži tiek novēroti arī opozicionāri izaicinošiem traucējumiem (OIT).

Introduction Attention deficit hyperactivity disorder (ADHD) is one of the most widespread types of psychical disorders in childhood which is spread all over the world. It is usually observed with school age children but can start already at pre-school age. The main characteristic features are inattentiveness and/or hyperactivity-impulsivity that is not corresponding age of the patient and his development level; thus disturbing social, academic/professional functioning of the individual. ADHD in childhood is very often observed with oppositional defiant disorders (ODD). Aim of the study To investigate and determine the most common types of ADHD expressions in age groups and with different genders. Materials and methods Questioning of class masters on expressions of ADHD (inattentiveness, hyperactivityimpulsivity) and ODD. There are 30 characteristics of expressions included in the questionnaire where answers for assessment of expression intensity are offered: never, sometimes, often and always. For processing of statistical data application software was used – MS Excel 2013. Results There were 100 children with ADHD involved in the research, age range from 4 to 12 – 70 boys and 30 girls (2,3/1). Children were divided into three age groups: (1) 4-6 year old, (2) 7-9 year old and (3) 10-12 year old. In general – the most often expression of ADHD was determined to be inattentiveness (71,2%). With boys the most common expression was observed in group aged 7-9 (67%), but with girls – aged 10-12 (53%). Hyperactivity-impulsivity expressions were observed rarer (64,7%). The most common hyperactivity-impulsivity symptoms were noticed with boys aged 7-9 (58%), whereas with girls aged 10-12 these symptoms were the rarest (24%). ODD expressions were noted the most rare (43%). The most common ODD expressions are observed with children at age group 4-6 – 31% of boys and 20% of girls. Conclusions When analysing received data, ADHD characterizes with its typical symptoms – inattentiveness and hyperactivity-impulsivity –, but in expressions of these symptoms we can observe differences between genders and age groups. With boys the most common expression of ADHD is inattentiveness symptoms, especially aged 7-9, whereas with girls – inattentiveness and hyperactivity-impulsivity symptoms are observed equally often, especially at the age 10-12. Key words Inattentiveness, hyperactivity/impulsivity, oppositional defiant disorders.
Expressions of attention deficit hyperactivity disorder (ADHD) with pre-school and younger school-age children at school
Keywords: Medicīna; Hiperaktivitāte; Imupulsivitāte; Neuzmanība; Opozicionāri; Izaicinoši